Mecanismo de tolerância a herbicidas inibidores da ALS em cultivares de aveia branca (Avena sativa L.) - Xavier, Elouize (2018)
World population growth and the consequent increase in demand for food is a troubling challenge for science. Increasing crop productivity is an important strategy to meet this challenge. Weed infestations are among the main limitations to the productivity of cultivated plants. The selectivity of herbicides to crops is fundamental to the success of weed control programs. White oats are an important crop for the southern region of Brazil. Research is fundamental to improve the safety of applications and to increase the number of herbicides and mechanisms of action available for this crop. Genetic, biochemical and phenotypic research was carried out to investigate the mechanism of tolerance to ALS inhibitor herbicides in white oat cultivars. For this, the cultivars of white oats UFRGS 14, UFRGS 18, URS Taura, URS Guará and URS Guria were used. The first chapter sought to characterize the level of tolerance of white oat cultivars to ALS inhibitor herbicides. The second chapter aimed to evaluate the level of weed control by the application of the herbicides penoxsulam and bispyribac. The third chapter aimed to evaluate the effect of the mefenpyr-methyl protector and metabolism inhibitors (organophosphorus insecticides) on the tolerance of white oat cultivars to the herbicide penoxsulam. The fourth chapter aimed to evaluate the activity of the ALS enzyme of white oat cultivars in the absence and presence of the enzymatic inhibitor herbicides imazethapyr and penoxsulam. The fifth chapter aimed to evaluate the activity of antioxidant enzymes superoxide dismutase and peroxidase in white oat cultivars by application of the herbicide penoxsulam. In the sixth chapter, using a sensitive and a tolerant white oat cultivar to the herbicide penoxsulam, the objective was to determine the activity of the enzyme glutathione-S-transferase (GST), reference gene stability (RT-qPCR) and expression of the cytochrome P450 and GST target genes. White oat cultivars showed different levels of tolerance to ALS inhibitor herbicides. The herbicide penoxsulam presented greater selectivity to the tested white oat cultivars. The herbicides bispyribac and penoxsulam presented levels of satisfactory control of ryegrass, an important winter weed crop. The use of organophosphate and mefenpyr-diethyl insecticides interfered in the tolerance levels of white oat cultivars to penoxsulam. The tolerance of white oat cultivars can not be attributed to the lower sensitivity of the ALS enzyme to the herbicides imazethapyr and penoxsulam. The activity of antioxidant enzymes may be a possible mechanism involved in tolerance to the herbicide penoxsulam. The results of action of inhibitors of plant metabolism and of enzymatic activity and gene expression of GST indicate that the herbicide metabolism is the responsible mechanism for the tolerance of the cultivars of white oats to penoxsulam.